Inhibition of sodium‐glucose cotransporter‐2 improves anaemia in mice and humans with sickle cell disease, and reduces infarct size in a murine stroke model - Wang, Jintao; Silaghi, Paul; Guo, Chiao; Harro, David; Eitzman, Daniel T. (Journal of cellular and molecular medicine, 2024)
Sodium‐glucose cotransporter‐2 (SGLT‐2) is expressed in the kidney and may contribute to anaemia and cardiovascular diseases. The effect of SGLT‐2 inhibition on anaemia and vascular endpoints in sickle cell disease (SCD) is unknown. A murine model of SCD was studied to determine the effects of the SGLT‐2 inhibitor, empagliflozin, on anaemia and stroke size. The University of Michigan's Precision Health Database was used to evaluate the effect of SGLT‐2 inhibitors on anaemia in humans with SCD. SCD mice treated with daily empagliflozin for 8 weeks demonstrated increases in haemoglobin, haematocrit, erythrocyte counts, reticulocyte percentage and erythropoietin compared to vehicle‐treated mice. Following photochemical‐induced thrombosis of the middle cerebral artery, mice treated with empagliflozin demonstrated reduced stroke size compared to vehicle treated mice. In the electronic health records analysis, haemoglobin, haematocrit and erythrocyte counts increased in human SCD subjects treated with an SGLT‐2 inhibitor. SGLT‐2 inhibitor treatment of humans and mice with SCD is associated with improvement in anaemic parameters. Empagliflozin treatment is also associated with reduced stroke size in SCD mice suggesting SGLT‐2 inhibitor treatment may be beneficial with regard to both anaemia and vascular complications in SCD patients.